(untitled) - Heiduk, Gunter (U.S.A., 1990)
Rev. papers originally presented at a symposium held in Duisburg, West Germany in Aug. 1987 which was sponsored by the Committee on Japanese Economic Studies of the United States and the Forschungsinstitut für Wirtschaftlich-Technische Entwicklungen in Japan und im Pazifikraum e.V. of Duisburg University. Includes bibliographical references and index.
Keywords: Technology and state,Nhà nước và công nghệ,Technology and state,Nhà nước và công nghệ,Technology and state; United States,Hoa Kỳ,Japan,Nhật Bản,Japan